The middle Eocene climatic optimum (MECO) event in the Contessa Highway section, Umbrian Apennines, Italy - Jovane, L.; Florindo, F.; Dinarès-Turell, J.; Sprovieri, M.; Marsili, A.; Coccioni, R.; Roberts, A.; Monechi, S. (Geological Society of America Bulletin, 2007)
We report a high-resolution paleomagnetic investigation constrained by new qualitative and semi-quantitative analyses of planktic and benthic foraminifera, nannofossil assemblages, integrated with oxygen and carbon isotope measurements, for the middle Eocene Scaglia limestones of the Contessa Highway section, central Italy. Calcareous plankton assemblages enable recognition of several biostratigraphic events from planktic foraminiferal Zone P11 to the lower part of Zone P15 and from calcareous nannofossil Zone NP15 to the upper part of Zone NP17, which results in refinement of the magnetobiostratigraphy of the Contessa Highway section. Correlation of the paleomagnetic polarity pattern with the geomagnetic polarity timescale provides a direct age interpretation for strata around the middle Eocene Scaglia limestones of the Contessa Highway section, from Chrons C21n (47 Ma) through to Subchron C18n.1n (38.5 Ma). Bulk carbon isotope values indicate a distinct carbon isotopic shift at 40 Ma that is interpreted to represent the first evidence in the northern hemisphere of the middle Eocene climatic optimum (MECO) that has recently been observed as a stable isotope anomaly in multiple records from the Indian-Atlantic sector of the Southern Ocean. This demonstrates a global response of the carbon cycle to the proposed transient increased pCO2 levels during the late middle Eocene and a consequent global CO2-driven climate change. Published 413-427 2.2. Laboratorio di paleomagnetismo JCR Journal reserved